The magic porridge pot:ladybird tales - Southgate, Vera; Sullivan, Colin (Ladybird London, 2006)
For over 40 years, this classic fairytale has delighted children and adults alike. This title combines a faithful retelling with rich, vibrant artwork, promising to reintroduce the magic of this timeless tale to those who loved it, while casting a spell upon a new generation of readers
This book is from English fiction shelf:E R:3